1991
DOI: 10.1007/bf00039658
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of yield stability of cowpea under sole and intercrop management in Nigeria

Abstract: Nine cowpea (Vigna unguiculata (L .) Walp .) breeding lines were grown in 13 experiments under sole crop and intercrop management, with and without insecticide application, in Nigeria . Cowpea was intercropped with cassava (Manihot esculenta Cranz), maize (Zea mays L.) and maize-cassava in the forest zone and with sorghum (Sorghum bicolor Moench .) and millet (Pennisetum glaucum (L .) R.Br.) in the savanna zone . Line by cropping system interactions were significant in 5 of 13 experiments and line by insectici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Although several studies on cowpea/maize intercropping undertaken elsewhere have been reported with varied intercrop advantages (Blade et al, 1992;Ezumah and Ikorgu, 1992;Singh and Ajeigbe, 2007;Katsaruware and Manyanhaire, 2009), emphasis on the use of short duration cowpea varieties has been negligible. In Southern Guinea Savanna region of Nigeria, there is dearth of documented information on cowpea/maize intercropping involving extra-early-and earlymaturing varieties of cowpea.…”
mentioning
confidence: 99%
“…Although several studies on cowpea/maize intercropping undertaken elsewhere have been reported with varied intercrop advantages (Blade et al, 1992;Ezumah and Ikorgu, 1992;Singh and Ajeigbe, 2007;Katsaruware and Manyanhaire, 2009), emphasis on the use of short duration cowpea varieties has been negligible. In Southern Guinea Savanna region of Nigeria, there is dearth of documented information on cowpea/maize intercropping involving extra-early-and earlymaturing varieties of cowpea.…”
mentioning
confidence: 99%
“…Stability of mixtures may be due to the positive effects of compensation, like production of more pods or heavier grains by a vigorous plant neighbouring a nonvigorous plant or reduced interaction with the environment [8][9][10]. Among nine cowpea breeding lines grown in 13 environments in Nigeria under different management regimes, Blade et al [15] noted that the stability of a given line was influenced more by the predictable effects of the treatments like cropping system and insecticide application than by the unpredictable variation among the environments.…”
Section: Discussionmentioning
confidence: 99%
“…Grain yields of two of four cowpea mixtures tested were more stable than those of their pure lines [14]. Blade et al [15] observe that the more stable cowpea lines tended to be low-yielding in both low-and high-yielding environments while the least stable lines out-yielded other lines in all except the poor environments.…”
Section: Introductionmentioning
confidence: 94%
“…The production of more leaves under monocropping and rotational cowpea means higher light interception and more photo-assimilate production (Babaji et al, 2011;Kouyate et al, 2012). Blade et al (1992) reported that cowpea growth was severely depressed by competition with other plants. The higher number of nodules per plant on cowpea planted at Taung may have been attributed to sandy soil on that site.…”
Section: Discussionmentioning
confidence: 99%